Lipoprotein lipase mediates an increase in selective uptake of HDL-associated cholesteryl esters by cells in culture independent of scavenger receptor BI - Franz Rinninger (Journal of Lipid Research, 2001)
Scavenger receptor class B type I (SR-BI) mediates the selective uptake of HDL cholesteryl esters (CEs) by the liver. LPL promotes this selective lipid uptake independent of lipolysis. In this study, the role of SR-BI in the mechanism of this LPL-mediated increase in selective CE uptake was explored. Baby hamster kidney (BHK) cells were transfected with the SR-BI cDNA, and significant SR-BI expression could be detected in immunoblots, whereas no SR-BI was visualized in control cells. Y1-BS1 murine adrenocortical cells were cultured without or with adrenocorticotropic hormone, and cells with no detectable or with SR-BI were obtained. These cells incubated without or with LPL in medium containing 125I/[3H]cholesteryl oleyl ether-labeled HDL3; tetrahydrolipstatin inhibited the catalytic activity of LPL. In BHK and in Y1-BS1 cells without or with SR-BI expression, apparent HDL3 selective CE uptake ([3H]CEt–125I) was detectable. Cellular SR-BI expression promoted HDL3 selective CE uptake by ~250–1,900%. In BHK or Y1-BS1 cells, LPL mediated an increase in apparent selective CE uptake. Quantitatively, this stimulating LPL effect was very similar in control cells and in cells with SR-BI expression. The uptake of radiolabeled HDL3 was also investigated in human embryonal kidney 293 (HEK 293) cells that are an established SR-BI-deficient cell model. LPL stimulated [3H]cholesteryl oleyl ether uptake from labeled HDL3 by HEK 293 cells substantially, showing that LPL can induce selective CE uptake from HDL3 independent of SR-BI. To explore the role of cell surface proteoglycans on lipoprotein uptake, we induced proteoglycan deficiency by heparinase treatment. Proteoglycan deficiency decreased the LPL-mediated promotion of HDL3 selective CE uptake. In summary, evidence is presented that the stimulating effect of LPL on HDL3 selective CE uptake is independent of SR-BI and lipolysis. However, cell surface proteoglycans are required for the LPL action on selective CE uptake. It is suggested that pathways distinct from SR-BI mediate selective CE uptake from HDL.—Rinninger, F., M. Brundert, I. Brosch, N. Donarski, R. M. Budzinski, and H. Greten. Lipoprotein lipase mediates an increase in selective uptake of HDL-associated cholesteryl esters by cells in culture independent of scavenger receptor BI.